2016
DOI: 10.1093/brain/aww109
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2 receptor gene variants and response to rasagiline in early Parkinson’s disease: a pharmacogenetic study

Abstract: The treatment of early Parkinson's disease with dopaminergic agents remains the mainstay of symptomatic therapy for this incurable neurodegenerative disorder. However, clinical responses to dopaminergic drugs vary substantially from person to person due to individual-, drug- and disease-related factors that may in part be genetically determined. Using clinical data and DNA samples ascertained through the largest placebo-controlled clinical trial of the monoamine oxidase B inhibitor, rasagiline (ClinicalTrials.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 54 publications
0
50
0
6
Order By: Relevance
“…In a first study, DNA samples from 692 participants of the ADAGIO study that represented the largest clinical trial of early stage PD patients under monotherapy with rasagiline were genetically stratified for 197 genetic polymorphisms from 20 candidate genes (Masellis et al 2016). The candidate genes were chosen by their involvement in rasagiline’s mode of action or metabolism or based on previously reported genetic association with PD in genome-wide association studies (GWAS).…”
Section: Stratification For Therapeutic Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a first study, DNA samples from 692 participants of the ADAGIO study that represented the largest clinical trial of early stage PD patients under monotherapy with rasagiline were genetically stratified for 197 genetic polymorphisms from 20 candidate genes (Masellis et al 2016). The candidate genes were chosen by their involvement in rasagiline’s mode of action or metabolism or based on previously reported genetic association with PD in genome-wide association studies (GWAS).…”
Section: Stratification For Therapeutic Outcomesmentioning
confidence: 99%
“…The candidate genes were chosen by their involvement in rasagiline’s mode of action or metabolism or based on previously reported genetic association with PD in genome-wide association studies (GWAS). The authors found a polymorphism in the dopamine D2 receptor gene as predictive for a meaningful clinical response to rasagiline treatment (Masellis et al 2016). This effect was not associated with the rate of symptom progression during the trial period.…”
Section: Stratification For Therapeutic Outcomesmentioning
confidence: 99%
“…In addition, single nucleotide polymorphisms rs2283265 and rs1076560 of the DRD2 gene have been reported to be significantly associated with a good response to rasagiline in early PD . Possible clinical implications are outlined in Table ; however, it must be pointed out that there are contradicting studies, and at this moment no definitive recommendations can be provided .…”
Section: Genetics and Pharmacogeneticsmentioning
confidence: 99%
“…53 While research is still in its early stages, recent work suggests that the presence of polymorphisms in the dopamine system in individuals with Parkinson disease may impact working memory and executive function 5456 and be related to changes in brain activation in cortico-striatal networks. 5759 Additionally, genotype may impact the effectiveness of dopamine drug therapies on motor symptoms 60, 61 and motor sequence learning 62 in those with Parkinson disease. Continued research is needed to fully understand the interaction between disease severity, drug therapies, motor behavior, and genotype in this clinical population and whether these interactions impact response to rehabilitation interventions.…”
Section: Genetic Polymorphisms Neuroplasticity and Motor Learningmentioning
confidence: 99%